Substance P up-regulates macrophage inflammatory protein-1 β expression in human T lymphocytes - Guo, Chang-Jiang (2002)
Substance P (SP) is an important modulator of neuroimmunoregulation. We have demonstrated that human T lymphocytes express SP and neurokinin-1 receptor (NK-1R), a primary SP receptor. In the present study, we investigated whether SP stimulates synthesis of macrophage inflammatory protein-1β (MIP-1β) in human T lymphocytes. SP significantly enhanced MIP-1β expression at both the mRNA and protein level in a human T cell line (Jurkat) containing the SP receptor gene (J-SPR) as determined by real-time PCR and ELISA assays. SP-induced MIP-1β expression is abrogated by the specific NK-1R antagonist (CP-96,345). The supernatants from SP-stimulated J-SPR T cell cultures enhanced T lymphocyte chemotaxis in vitro, indicating functional activity of SP-induced MIP-1β. In addition, SP augmented secretion of MIP-1β from primary cultures of peripheral blood lymphocytes (PBL) isolated from some of the donors. This donor variability was due to differential expression of the primary SP receptor (NK-1R) on PBL from different donors. PBL from two of seven donors that did not respond to SP stimulation had undetectable NK-1R expression. Our mechanistic studies showed that SP activated NF-κB promoter-directed luciferase activity, which may be responsible for its effect on MIP-1β expression in human T cells. Our data provide a potential mechanism by which SP selectively influences cellular immune responses such as β-chemokine expression in human T lymphocytes through NK-1R, which may have an important in vivo implication in inflammatory diseases.